PENERAPAN METODE FISHBONE DIAGRAM AND 5 WYH’S ANALYSIS UNTUK MENINGKATKAN KUALITAS PRODUK PAKAIAN JADI - Santoso, Sugeng; Sarnadi; Apriasty, Ika (Jurnal Visionida, 2022)
The Indonesian apparel industries have challenge compared to competitors from other countries, such as China, Vietnam and Bangladesh. These countries have advantages such as cheap on raw materials, costs of production and international trade agreement schemes. However, the apparel industry in Indonesia can have other advantages, one of which is quality of product. The purpose of this study is to analyze the processes carried out in effort to improve quality of product by decreasing the defect rate through the formulation of an appropriate root cause analysis. The research uses a quantitative and qualitative approach, using the fishbone diagram method, 5 why’s analysis and A3 templates, while the qualitative approach is carried out by interviewing the vendor to gain experience of the benefits before and after the application of the methods. Comparison of the average final inspection data from all vendors producing products of brand apparel XYZ before and after the application of the fishbone analysis method and 5 why’s diagrams using the A3 template. The results showed an increase in the quality of apparel products with a decrease in the defect rate that caused the company’s quality rating increased and also increased the ownership or a sense of responsibility for the quality of all parts, building a quality culture or culture of quality within the company, improving communication and coordination within the company